Assessment of Nexus between energy consumption and sustainable development in Russian Federation: A disaggregate analysis. (2022) - Monirul Islam, Md.; Sohag, Kazi; Shahbaz, Muhammad
Highlights: Studies an energy resource-sustainable development nexus in Russian Federation. Uses augmented ARDL and dynamic ARDL simulation models for data analysis. Finds a long-term positive influence of renewable energy and financial openness. Detects a hostile role of non-renewable energy, urbanization and political terror scale. Suggests a shift to the modest use of renewables to accelerate sustainable development. Abstract: Russia's competitiveness and productivity encounter the intense environmental challenges due to the reckless fossil fuel consumption, putting this country's long-run sustainability at risk. Despite this, this country intends to achieve the sustainable development goal by cutting greenhouse gas (GHG) emissions to 70% of its 1990 level as pledged in the Paris Agreement in 2016. This research assesses the relationship between disaggregate (renewable and non-renewable) energy consumption and sustainable development within the purview of financial, demographic and country risk indicators using annual time-series data from 1990 to 2020. This paper utilizes an augmented ARDL approach to co-integration and a dynamic ARDL simulation model to detect counterfactual forecasting shocks to the predictor variables and their effects on the predicted indicator. The study's findings divulge that renewable energy consumption escalates the sustainable development in the long run, whereas non-renewable energy consumption declines. Then again, urbanization and political terror scale (PTS) have a long-term adverse effect on sustainable development. On the other hand, financial openness substantially exerts a favorable long-term influence on sustainable development. Therefore, this study suggests shifting to generous renewable energy usage to ease the adverse effect of non-renewable energy consumption on the sustainable development in Russia. Graphical abstract: Image, graphical abstract